Gait and electromyographic analysis of anterior cruciate ligament deficient subjects - Beard, D; Soundarapandian, R; O'Connor, J; Dodd, C (1996)
Some anterior cruciate ligament deficient (ACLD) patients can overcome passive sagittal joint laxity and maintain dynamic stability of the knee joint. Gait analysis with electromyographic (EMG) support was used in an attempt to identify mechanisms whereby ACLD individuals achieve this functional stability. A group of 18 patients with arthroscopically proven, unilateral, chronic (> 6 months) ACLD had their gait assessed using a three-dimensional VICON gait analysis system. Simultaneous quadriceps, hamstrings and gastrocnemius muscle activity was recorded using surface electromyography. Values of minimum knee flexion angle and activity duration of leg musculature were calculated for each section of stance phase and compared to a group of nine matched controls. The minimum flexion angle at heel contact and mid-stance was larger for the ACLD group than in controls. Throughout stance phase, the ACLD patients had increased hamstrings activity duration compared to the controls. Quadriceps activity duration was similar in both groups. It was found that the duration of hamstring activity correlated with the flexion angle at foot contact. The similarity in quadriceps activity between groups implies that the previously reported net increase in internal flexion moment observed in ACLD patients during stance phase may not necessarily be due to decreased activity of the quadriceps. Net increase in internal flexion moment may be achieved by the observed increase in hamstrings activity. Mechanisms and reasons why ACLD patients maintain increased knee flexion angles in stance phase are discussed.